Aqueous extract of purple nutsedge bulbs on germination and initial growth of radish seedlings - Cavalcante, Jerffeson Araujo; Lopes, Kilson Pinheiro; Pereira, Natali Almeida Evangelista; Silva, Joseano Graciliano; Pinheiro, Romário Mesquita; Marques, Robson Luiz Legorio (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2018)
This study aimed to evaluate the effect of different concentrations of aqueous extract of purple nutsedge bulbs (Cyperus rotundus L.) compared to indole-3-butyric acid (AIB) on the germination and early growth of radish seedlings. Two experiments were conducted in both were used completely randomized design with four replications of 50 seeds for germination and 20 seeds for the length of the primary root. In the first experiment, radish seeds were treated with concentrations of zero, 0.5, 1.0, 1.5 mg L-1 of AIB. In the second experiment, the radish seeds were subjected to concentrations of zero 15, 25, 50 and 100% of the aqueous extract of purple nutsedge bulbs, confronted with the best concentration obtained from synthetic auxin. In both experiments, the seeds were soaked in each solution for five minutes. Evaluations consisted of the germination test, first counting of germination, germination speed index and length of primary root. The data were subjected to analysis of variance; means were compared by Tukey test at 5% probability and polynomial regression. The AIB allow better physiological performance of radish seeds, being that 1.5 mg L-1 was the better concentration employed. The aqueous extract of purple nutsedge stimulates germination and early development of radish seedlings when their seeds are soaked in concentrations around 25%, similarly to the results obtained when employing the AIB.